2021
DOI: 10.3389/fnhum.2020.584312
|View full text |Cite
|
Sign up to set email alerts
|

Dance on the Brain: Enhancing Intra- and Inter-Brain Synchrony

Abstract: Dance has traditionally been viewed from a Eurocentric perspective as a mode of self-expression that involves the human body moving through space, performed for the purposes of art, and viewed by an audience. In this Hypothesis and Theory article, we synthesize findings from anthropology, sociology, psychology, dance pedagogy, and neuroscience to propose The Synchronicity Hypothesis of Dance, which states that humans dance to enhance both intra- and inter-brain synchrony. We outline a neurocentric definition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 296 publications
(219 reference statements)
7
68
0
2
Order By: Relevance
“…These abilities are of prime importance in social interactions and therefore in the formation and maintenance of social groups. This supports evolutionary theories of the importance of dance in enhancing "brain networks that support our ability to understand others, i.e., our interpersonal coordination skills" (Basso et al, 2021).…”
Section: Observationsupporting
confidence: 75%
See 1 more Smart Citation
“…These abilities are of prime importance in social interactions and therefore in the formation and maintenance of social groups. This supports evolutionary theories of the importance of dance in enhancing "brain networks that support our ability to understand others, i.e., our interpersonal coordination skills" (Basso et al, 2021).…”
Section: Observationsupporting
confidence: 75%
“…Karpati and colleagues published a review in 2015 (Karpati et al, 2015), but it was not intended to be comprehensive. Basso and colleagues' 2021 article (Basso et al, 2021) also contains useful material, but this is a "Hypothesis and Theory" article, and was not intended to provide a review of the neuroscience of dance.…”
Section: Introductionmentioning
confidence: 99%
“…One interesting example is reported by a recent publication by Wassiliwizky and colleagues, in which it is demonstrated that, although poetry can elicit strong emotional responses in an analogous way as those observed when listening to music, the role of the nucleus accumbens and the whole neural circuitry appears different [170]. Moreover, the sharing of symbolic meaning and rhythm among speech, music and dance may be even better disentangled through novel transdisciplinary studies [171,172].…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Motor imagery (MI) is related to the process of mentally generating a quasi-perceptual experience in the absence of any appropriate external stimuli [ 1 ]. MI practice promotes children’s motor learning and has been suggested to provide benefits in enhancing the musicality of untrained children [ 2 , 3 ], in evaluating the screen-time and cognitive development [ 4 ], and improving attentional focus and rehabilitation [ 5 , 6 , 7 ], among others. MI-based brain–computer interface (BCI) systems often entail electroencephalogram (EEG)-decoding because of their ease of use, safety, high portability, relatively low cost, and, most importantly, high temporal resolution [ 8 ].…”
Section: Introductionmentioning
confidence: 99%